Developmental change in the gene expression of transient receptor potential melastatin channel 3 (TRPM3) in murine lacrimal gland - Kanewska, A.; Ito, M.; Karasawa, Y.; Inada, M.; Garreis, Fabian; Paulsen, Friedrich; Takeuchi, M. (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Transient receptor potential (TRP) channels are cation channels with ubiquitous expression. Various TRP channels are functionally active at the ocular surface and are involved in tear secretion and multiple inflammatory processes. So far, the impact of TRP channels regarding the development of the lacrimal gland (LG) is unclear. While investigating TRP channels in the LG, the TRPM3 channel presented itself as a promising candidate to play a role in the development and functioning of the LG. Therefore, Trpm3 expression was analyzed in different embryonic and postembryonic LGs. Thus, gene expression of TRPM channels including Trpm2, Trpm3, Trpm4 and Trpm6 was analyzed by quantitative RT-PCR in murine LGs at different developmental stages. Localization of TRPM3 in LGs was examined by immunohistochemistry. Primary LG epithelial cells (LGEC) and mesenchymal cells (MC) from newborn mice were cultured (either separately or collectively) for three days, and Trpm3 expression was analyzed in LGEC and MC. As a result, gene expression of Trpm2, Trpm4 and Trpm6 showed no significant difference in LGs in the different stages of development. However, Trpm3 gene expression was significantly higher in the embryonic stage than in the postnatal stage with the peak at E18. Postnatal, Trpm3 expression significantly decreased up to 28-fold until two years of age. Immunohistochemistry for TRPM3 revealed apical membranous expression in the excretory ducts, as well as in the acini of up to P7 old mice. Trpm3 expression in LGEC were significantly higher than that of MC. Our results indicate that Trpm3 expression in murine LG is age-dependent and peaks at age E18. Its expression is localized in the apical membrane of the glandular epithelium. However, its functional role still requires additional study in the LG.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Development; Lacrimal gland; Ocular surface; Ophthalmology; TRP channels